Study on the effect of acid fracturing fluid on pore structure of middle to high rank coal - Zhao Kang; Li Liangwei; Li Kun; Zuo Shaojie; Jiang Zhizhong (Scientific Reports)
Abstract Acid fracturing fluids can effectively improve the microporous structure of coal, thereby enhancing the permeability of coal seam and the efficiency of gas drainage. To explore the effects of acid fracturing fluids on the pore structure modification of coal samples from different coal ranks, hydrochloric acid-based acid fracturing fluids were prepared and used to soak four types of medium to high-rank coal in an experiment. High-pressure mercury intrusion and liquid nitrogen adsorption techniques results demonstrated that the acid fracturing fluid can effectively alter the pore structure of coal. However, the modification effect does not exhibit a linear relationship with coal rank. The porosity of fat coal and coking coal increased by approximately 30%, while the surface area of gas coal and fat coal increased by about 20%. The new micropores produced by the acid fracturing fluid will increase the roughness of the fracture surface, but the widening of the original fracture will reduce the tortuosity of the fracture. Only the fractal dimension of lean coal has a significant change, about 6%. Overall, acid fracturing fluid has the best effect on gas coal and coking coal. The research results provide a reference for the selection and application of acid fracturing fluid in coal seam hydraulic fracturing.